Pendampingan Literasi Keuangan Digital Bagi UMKM Digital Di Kelurahan Tembong Kota Serang - Sev Rahmiyanti; Bambang Arianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The era of digitalization makes the use of digital financial applications contribute to the development of MSME businesses, especially from a financial aspect. MSME activists can actually use advances in digital financial technology to finance and strengthen business capital. However, the lack of digital financial literacy makes it difficult for MSME activists, especially digital ones, to use digital financial services properly, so that many are exposed to illegal online loans. In community service in the Tembong Village, Serang City which was held on 5th March 2023, assistance was provided on the importance of digital financial literacy for digital-based MSME activists. From the results of this activity it is known that MSME activists still have low understanding regarding digital financial literacy. This makes it difficult for some digital MSME activists to develop and worsens business performance. The success of this activity can be seen from digital MSME activists who have utilized various digital financial applications to increase working capital through digital financial financing patterns. MSME activists can also get to know digital financial governance, so they can carry out digital transactions as an effort to strengthen the financial aspects and digital business ecosystem.